2015
DOI: 10.11648/j.ijnfs.s.2015040101.14
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Some Pharmacological Effects of Caffeine and Taurine in Food Supplements

Abstract: Abstract:In modern times in all age groups energy supplements containing different amounts of Caffeine and Taurine are applied. Caffeine is purine alkaloid, which stimulates central nervous system action, enhances the strength and frequency of the cardiac contractions and increases the excretion of urine. Taurine is a sulfur containing amino acid, which possesses many fundamental biological roles including: effect on synaptic transmission in the central nervous system, cardiotropic action, antioxidant and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Low protein intake is associated with loss of bone mineral density in the thigh and spine. Adequate calcium intake is required to achieve the beneficial effect of the protein on bone mineral density (Tsvetkova et al 2015).…”
Section: Healthy Eatingmentioning
confidence: 99%
“…Low protein intake is associated with loss of bone mineral density in the thigh and spine. Adequate calcium intake is required to achieve the beneficial effect of the protein on bone mineral density (Tsvetkova et al 2015).…”
Section: Healthy Eatingmentioning
confidence: 99%
“…The main ingredients of energy drinks are caffeine, taurine, vitamins, carbohydrates, and other ingredients such as tyrosine, citicoline and guarana [2]. These compounds stimulate brain activity, memory and attention [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is essential to control the maximum limits of taurine in beverage and food. The European Authority for Food Safety reported that, acute health and fatal problems occurred due to Omer et al / HPLC Methods for Analysis of Taurine in Energy Drinks 2 / 8 the high consumption of energy supplements [3]. Therefore, development and validation of accurate analytical methods for analysis of taurine in energy drinks is very important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings provide the first information related to taurine impact on bone microarchitecture after prolonged supplemental use. Adverse effects of taurine (in high concentrations) on brain activity have also been demonstrated (Tsvetkova et al 2015). Taurine is known to be an inhibitory neurotransmitter and neuromodulator.…”
mentioning
confidence: 99%